MAHADEVI VARMA’S LIFE, CONTRIBUTION AND LITERARY LEGACY - Sharma, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focuses on the life, contribution and literary legacy of Mahadevi Varma, who is known as ’Meera of the modern age’ in modern Hindi literature. She became a prominent signature of Hindi literature due to her significant contribution to the Chhayavaad poetry stream. Themes such as love, suffering, unity of the inanimate and the conscious, aesthetic feeling and mysticism are prominent in her writings. This study analyses her poetry and prose works, including her famous poetry collections such as Yama, Rashmi, Neerja etc., and highlights the symbolism and deep mentality in her writings. Mahadevi Varma made significant contributions not only in poetry but also in prose genres such as essays, sketches and memoirs. Her literature not only depicts personal emotions but also shows her deep sensitivity and awareness towards society and culture. Additionally, the study also highlights her awards and national honours, including the Padma Bhushan, Padma Vibhushan and Jnanpith awards. This study highlights Mahadevi Varma’s literary influence and her invaluable contribution to Hindi literature. Her writings gave a new direction to Hindi literature and her works are still alive among readers.